Targeting Integrin and Integrin Signaling in Treating Thrombosis. Issue 1 (January 2015) - Estevez, Brian; Shen, Bo; Du, Xiaoping
<x xml:space="preserve">Abstract</x> The critical roles of integrins in thrombosis have enabled the successful development and clinical use of the first generation of integrin antagonists as represented by abciximab (Reopro), eptifibatide (Integrilin), and tirofiban (Aggrastat). These integrin αIIbβ3 antagonists are not only potent antithrombotics but also have significant side effects. In particular, their induction of ligand-induced integrin conformational changes is associated with thrombocytopenia. Increased bleeding risk prevents integrin antagonists from being used at higher doses and in patients at risk for bleeding. To address the ligand-induced conformational changes caused by current integrin antagonists, compounds that minimally induce conformational changes in integrin αIIbβ3 have been developed. Recent studies on the mechanisms of integrin signaling suggest that selectively targeting integrin outside-in signaling mechanisms allows for potent inhibition of thrombosis, while maintaining hemostasis in animal models.